Mindfulness and the intention-behavior relationship within the theory of planned behavior - Chatzisarantis, Nikos L. D.; Hagger, Martin S. (2007)
The present study examined moderating effects of mindfulness on the intention-behavior relationship within the theory of planned behavior. Mindfulness describes a quality of consciousness characterized by heightened clarity and awareness of present experiences and functioning. Study 1 showed that mindfulness moderated the intention-behavior relationship in a leisure-time physical activity context such that intentions predicted physical activity among mindful individuals and not among less-mindful individuals. Study 2 measured counterintentional habits relating to binge-drinking and found that habitual binge-drinking obstructed the enactment of physical activity intentions among individuals acting less mindfully but not among individuals acting mindfully. Finally, Studies 1 and 2 demonstrated that the effects of mindfulness on physical activity were independent of effects observed for habit and variables contained in the theory of planned behavior. These findings suggest that mindfulness is a useful construct that helps understand the intention-behavior relationship within the theory of planned behavior.
Photocopy.
Includes bibliographical references (pages 675-676).
Keywords: Intention-behavior.; Planned behavior -- Theory; Mindfulness